Influenza immunization coverage for healthcare workers in a community hospital in Qatar (2011-2012 and 2012-2013 seasons) - Humberto Guanche Garcell; Eduardo Crespo Ramirez (Elsevier, 2014)
Summary: Influenza vaccination is recommended for all healthcare workers (HCW) to prevent transmission within healthcare facilities. We conducted a descriptive study on influenza vaccination coverage during 2011-2012 and 2012-2013 campaigns in a community hospital in Qatar. 61.7% of the HCW were immunized in the first campaign, with an increase of up to 71.1% (p < 0.05) in the second one, which was mainly due to better compliance of doctors (46.9% and 69.2%, respectively). Our results show proper coverage rates according US standards and highlight the need to implement additional strategies to improve health workers adherence of influenza, vaccination. Keywords: Influenza, Immunization coverage, Healthcare workers, Qatar